Panggilan Keterikatan Kerja Dan Kepuasan Kerja Pada Guru - Thasya Fatharani; Missiliana Riasnugrahani (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
This study aims to examine whether work engagement can strengthen the relationship between calling and job satisfaction. Analysis with Hayes mediation model 4 shows that work engagement does not mediate the relationship between calling and job satisfaction. The job satisfaction of teachers is only related to their calling in the workplace. Teachers who see their work as having a positive contribution to the students will feel that their work has a deep meaning, so they are more satisfied. Meanwhile, teachers who are engaged with their careers are not always satisfied with their jobs. In sum, calling is an essential source of teachers feeling engaged and satisfied with their work. Teachers who perceive their job as calling will feel job satisfaction and show dedication and enthusiasm at work.